Relation of Endothelin-1 and Malondialdehyde with Pre-eclampsia in Pregnant Women (Indian Journal of Forensic Medicine & Toxicology, 2020)
A case-control study was conducted in Kirkuk city in Kirkuk general hospital from first of March 2018 andto end of September 2018 to evaluate the role of endothelin-1 and malondialdehyde in pathogenesis of preeclampsia in pregnant women. The study included 30 pregnant women with preeclampsia, patients weredefined and divided according to the National High Blood Pressure Education Program Working Group onHigh Blood Pressure in Pregnancy. A control group of 30 healthy normotensive pregnant females was alsoincluded. All comparison groups were matched for mother’s age, parity, and gestational age at the time ofenrollment and blood collection. Three ml of blood was collected by vein puncture, blood samples wereplaced into sterile test tubes and left for 30 minutes at 37 °C then were centrifuged at 3000 rpm for 15minutes then the clot was removed and the obtained sera were then aspirated using automatic micropipetteand transferred into clean test tubes and stored in deep freeze at -20°C for determination of endothelin-1 andmalondialdehyde by usingELISA technique. The study showed that the highest mean level of endothelin-1was found in pregnant women with pre-eclampsia(13.15±2.81 pg/ml) and the lowest mean was in thecontrol group (0.41±0.31 pg/ml). The result was highly significant (P<0.01). The study showed that thehighest mean level of MDA was found in pregnant women with pre-eclampsia (6.75±2.94 nmol/ml) andthe lowest mean was recorded in the control group (3.85±1.29 nmol/ml). The result was highly significant(P<0.01). The current study showed that the mean age of patients enrolled in the study was 33.5 years, thehighest mean of endothelin-1 in HD patients was recorded within the age group 20-29 year of pregnantwomen with pre-eclampsia. Although the results was non-significant. The study showed positive correlationbetween endothelin-1 and MDA levels pregnant women with pre-eclampsia. It was concluded that serumendothelin-1 and MDA levels were highly correlated with pregnant women with pre-eclampsia